The effect of the school literacy movement on the reading skills of third-grade students at SDN 2 matangaji - Lastriyani, Rifani Dwi; Labudasari, Erna; Iman, Bagus Nurul (Lembaga Teewan Journal Solutions, 2026)
The effect of the implementation of the School Literacy Movement on the reading skills of grade III students at SDN 2 Matangaji is the main focus of this study. The research background is based on differences in reading competence between students, both in the aspects of reading fluency, simple word recognition, pronunciation of consonants and vowels, and understanding the content of reading. The quantitative approach was applied through a pre-experimental method with a one-group pretest-posttest design, with 21 students as a sample. Data collection was carried out using reading competency tests before and after treatment and observation of literacy activities that took place. Treatment is given in the form of reading habits for fifteen minutes before the learning begins and combined with learning Indonesian on the main idea, material and supporting ideas. The results of data processing proved that the average value before treatment reached 69.31 and increased to 84.55 after treatment was given. The Shapiro–Wilk normality test shows that the posttest and pretest data are distributed normally. In addition, the research instrument has good reliability, as shown by Cronbach's Alpha value of 0.783 in the pretest and 0.979 in the posttest. According to the results of the paired sample t-test, a significance value was obtained below 0.05 until there was a significant difference between reading competence after and before treatment. These findings prove that the implementation of the School Literacy Movement is effective in optimizing students' reading competence.